Status of the Implementation of Alternative Learning System in Jalajala Elementary School - Besmonte, Ederlinda SJ. (Future Science / FSH-PH Publications, 2023)
The study aimed to assess the status of the implementation of Alternative Learning System (ALS) in Jalajala Elementary School during the School Year 2021-2022. The study considered 148 ALS learners in the said school. Purposive sampling technique was used. The respondents were described in terms of their age, sex, civil status, educational attainment, and monthly family income. Descriptive survey research design was used. A researcher-made questionnaire-checklist was utilized to assess the implementation of Alternative Learning System (ALS) in public elementary schools with respect to teaching methodologies, instructional materials, and evaluative techniques. Problems encountered in the status of the implementation of Alternative Learning System were also determined. The study revealed that the ALS learners are mostly on their maturity ages and predominantly males. Most of them are single; have monthly income below Php 10,000 and mostly are high school undergraduates and elementary undergraduates. Alternative Learning System is often implemented with respect to teaching methodologies, instructional materials and evaluative techniques as evaluated by ALS learners. No significant difference exists on the perception of the respondents on the implementation of Alternative Learning System with respect to teaching methodologies, instructional materials, and evaluative techniques in terms of age, sex, civil status, educational attainment, and monthly family income. The most common problems encountered by ALS learners on the implementation of Alternative Learning System are family problems, marital problem, and school too far from home and financial problem as well. Some of the recommendations include continuous implementation of the programs in ALS, provision of better co-curricular programs, purchasing of needed facilities and equipment, and provision of opportunities to ALS graduates.